Challenges And Opportunities For Implementing Student-Centered Learning Methods At Koinonia Sentani High School - Kabanga, Lewi; Tabuni, Simon; Yikwa, Yulies Yustinus (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Abstract The SCL method collaborates with learning that focuses on the context and needs of students. In its implementation, it requires the nature of constructive learning. The purpose of this study is to investigate the Challenges and Opportunities of Koinonia-Sentani High School in applying the SCL Method, especially in the application of Christian Religious Education learning. The method used was a qualitative descriptive method. Data were obtained from field observations, interviews, and document reviews. In validating the data, the triagulation technique of the data source was used. The results of this study show that the adaptation of the SCL method for students at Koinonia Sentani High School experiences challenges and opportunities to optimize it. These challenges are student learning readiness and resource utilization. Learning readiness is motivated by physical, mental, and emotional-social factors. Meanwhile, the use of resources is in the form of technology integration, teacher and student participation, and methods. In addition to challenges, there are also opportunities to apply the SCL method, namely school regulations and cultures that are resilient to the balance of tradition and global challenges. This research is expected to contribute to changes related to the implementation of constructive learning through the SCL method that focuses on student needs.